2020
DOI: 10.3389/fendo.2020.604648
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Inhibits Endometriosis Through Suppression of Estrogen Receptor β Signaling Pathway

Abstract: Endometriosis is an inflammatory gynecological disorder characterized by endometrial tissue growth located outside of the uterine cavity in addition to chronic pelvic pain and infertility. In this study, we aim to develop a potential therapeutic treatment based on the pathogenesis and mechanism of Endometriosis. Our preliminary data showed that the expression of estrogen receptor β (ERβ) was significantly increased, while ERα was significantly decreased, in endometriotic cells compared to normal endometrial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The estrogen-related receptors (ERRs) are another possible factor for controlling pyruvate metabolism, resulting in the stimulated transcription of PDK2 and PDK4 ( Zhang et al, 2006 ; Jeong et al, 2012 ). Several studies have suggested that P. vulgaris possesses estrogen resistant properties ( Huang et al, 2006 ; Collins et al, 2009 ; Kim et al, 2014 ; Xiang et al, 2020 ). However, in our study, we observed that PV regulates the expression of PDK1/3 and activity of LDHA beside of anti-estrogenic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estrogen-related receptors (ERRs) are another possible factor for controlling pyruvate metabolism, resulting in the stimulated transcription of PDK2 and PDK4 ( Zhang et al, 2006 ; Jeong et al, 2012 ). Several studies have suggested that P. vulgaris possesses estrogen resistant properties ( Huang et al, 2006 ; Collins et al, 2009 ; Kim et al, 2014 ; Xiang et al, 2020 ). However, in our study, we observed that PV regulates the expression of PDK1/3 and activity of LDHA beside of anti-estrogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of enzymes related to glucose metabolism, such as enolase 1 and M2-type pyruvate kinase, can be decreased with P. vulgaris treatment ( Wang et al, 2014 ). Several studies have demonstrated that P. vulgaris and betulinic acid, one of its active ingredients, have an inhibitory effect on the growth of endometrial cells through anti-estrogenic activity ( Huang et al, 2006 ; Collins et al, 2009 ; Xiang et al, 2020 ). However, the molecular mechanisms underlying the inhibition of endometriosis by P. vulgaris have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of BA on epigenetic gene expression was rarely investigated, a single study reported that BA treatment caused a suppression in ERβ expression through epigenetic modi cation of its promoter in endometriotic cells (41). To investigate if alteration of cellular epigenetics might contribute to the antitumor activity of BA, we examined the methylation status of the promoter region of two target genes in the Kaiso signaling pathway, a known oncogene; c-Myc, and a tumor suppressor gene; CDKN2A.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is a gynecological inflammatory disease that affects between 5% and 10% of women during the reproductive phase; in endometriosis, an increase in the overexpression of estrogen receptor β (ER-β) compared with estrogen receptor α (ER-α) has been reported, which promotes endometriotic cell proliferation and inflammation. BA was found to suppress ER-β expression by targeting ER-β promoter genes that further induced apoptosis in endometriotic cells and decreased the production of pro-inflammatory cytokines including IL-1β, IL-6, and TNF-α [ 95 ].…”
Section: Betulinic Acidmentioning
confidence: 99%